Educational Management in the Digital Age: Integrating Technology for Student Success - Sofwan Manaf (STAI Hubbulwathan Duri, 2024)
In the contemporary educational landscape, the integration of technology has become imperative for fostering student success. This article explores the dynamics of educational management in the digital age, emphasizing the pivotal role of technology in shaping and enhancing learning environments. The study adopts a literature review methodology to systematically analyze existing research, theoretical frameworks, and practical implementations related to educational technology and management. The literature review (from 2015-2024) covers key themes such as the impact of digital tools on pedagogy, the role of educational leaders in fostering technological integration, and the challenges and opportunities associated with managing a technology-enhanced educational ecosystem. By synthesizing current literature, the article provides insights into effective strategies for educational leaders to navigate the complexities of digital integration, fostering an environment conducive to student success. The findings underscore the need for a comprehensive approach to educational management that embraces technology as a catalyst for innovation and learning. This article contributes to the discourse on educational technology and management, offering valuable perspectives for educators, administrators, and policymakers seeking to harness the full potential of technology in the pursuit of academic excellence.